Integrated crucible preform based on single-layer structure

By spraying resin on the surface of the carbon fiber mesh tire layer, a single-layer structure integrated crucible prefabricated body with alternating superposition structures is solved, and the service life and preparation efficiency of crucible products are improved.

CN119571440APending Publication Date: 2025-03-07XIAN CHAOMA SCI TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411569302.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prefabricated body in the integrated carbon/carbon composite crucible has a poor bonding problem with the subsequent functional coating, which affects the service life of the crucible product.

Method used

An integrated crucible prefabricated body based on a single-layer structure is adopted, and the alternating superposition structure is formed by spraying resin on the surface of the carbon fiber mesh tire layer to ensure a good combination of the prefabricated body and the subsequent functional coating.

Benefits of technology

It improves the service life of crucible products and simplifies the preparation process of the prefabricated body, ensuring good bonding performance between the functional coating and the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571440A_ABST
    Figure CN119571440A_ABST
Patent Text Reader

Abstract

The invention relates to an integrated crucible preform based on a single-layer structure, and belongs to the technical field of thermal field components for monocrystalline silicon. The prefabricated body is prepared by needling and layering pure net tires sprayed with resin, namely, the prefabricated body is of an alternate overlapping structure of net tire layers and resin layers, and the resin layers can play a mechanical supporting role between the net tire layers, so that the mechanical property of the integrated crucible prefabricated body prepared on the basis of the single-layer structure of the pure net tires is improved, and the service life of the prefabricated body is prolonged. In addition, the structure of the prefabricated body can be hardened and not prone to deformation, transportation and storage are more facilitated, the pure net tire layer which is uniform and isotropic serves as the inner surface of the integrated crucible prefabricated body, certain roughness and uniform apparent mass are achieved, preparation of a subsequent functional coating is facilitated, and the service life of the prefabricated body is prolonged. In addition, the bonding performance of the functional coating and the crucible base body is improved, and the problem that the service life of a crucible product is affected due to the fact that the functional coating is prone to falling off is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an integrated crucible preform based on a single-layer structure, belonging to the technical field of thermal field components for single crystal silicon. Background Art

[0002] The single crystal silicon pulling furnace used in traditional single crystal silicon pulling is usually composed of a carbon / carbon crucible and a quartz crucible, that is, the quartz crucible is nested in the carbon / carbon crucible. The quartz crucible plays the role of carrying silicon materials to ensure the purity of silicon materials, while the carbon / carbon crucible plays the role of carrying the quartz crucible and providing strength support. The temperature inside the single crystal silicon pulling furnace is as high as 1500℃. The quartz crucible holding the silicon materials will have problems such as deformation and softening, and replacement is very frequent. About 1 carbon / carbon crucible will consume 12 to 18 quartz crucibles. In addition, the raw material quartz sand for the production of quartz crucibles is relatively scarce. In recent years, the rapid increase in the price of high-purity quartz sand and the imbalance between supply and demand have led to high crystal pulling costs.

[0003] Carbon / carbon composite materials are composite materials formed by carbon fiber or various carbon fabrics reinforced with carbon matrix. They have excellent properties such as low density, high specific strength, wear resistance, and high temperature resistance. They are currently widely used in aerospace, metallurgy, new energy and other fields. At present, researchers have proposed the use of "integrated carbon / carbon composite crucibles" to replace the traditional "combination of carbon / carbon crucibles and quartz crucibles". On the one hand, it can avoid the impact of the rapid rise in the price of high-purity quartz sand and reduce the material cost of crystal pulling. On the other hand, the integrated design can combine materials and performance into one, maximize its advantages, and further reduce product costs.

[0004] The integrated carbon / carbon composite crucible is obtained by densifying a carbon fiber preform and combining it with a high-performance coating on the surface. Among them, the carbon fiber preform is the blank for preparing the carbon / carbon composite crucible, which directly affects the service life of the crucible product. The carbon fiber preform is usually composed of carbon fiber woven cloth, carbon fiber mesh and carbon fiber filaments. For example, patent CN 111002435A discloses a weaving process for a carbon-carbon crucible preform for a single crystal silicon furnace, first laying a layer of plain cloth on the tooling, then laying a layer of mesh, and then evenly winding with fiber filaments in the horizontal and vertical directions, and then needle punching, and repeating this until the preform is completed; patent CN215250466U discloses a carbon / carbon / silicon carbide composite crucible preform, including carbon fiber plain cloth, carbon fiber mesh and carbon fiber filaments, the carbon fiber mesh is laid on the carbon fiber plain cloth to form a layer unit, the carbon fiber filaments are cross-wound on the outside of each layer of the layer unit along the inclined direction, and each layer unit is stacked layer by layer to a predetermined thickness, and needle punching and stitching are performed in the thickness direction to form a crucible preform. Although the above-mentioned carbon fiber preform has high mechanical strength and good shaping effect, due to the presence of carbon fiber woven cloth on its inner surface, the surface roughness is low and the bonding with subsequent functional coating is poor, which will greatly affect the service life of the crucible product. Summary of the invention

[0005] In view of the problem that the preform in the current integrated carbon / carbon composite material crucible has poor bonding with the subsequent functional coating, the present invention provides an integrated crucible preform based on a single-layer structure. The preform is prepared by pure mesh needle-punching and resin spraying, and the overall structure is nearly isotropic, which not only ensures the mechanical strength of the preform, but also ensures a good bonding effect with the subsequent functional coating, thereby increasing the service life of the crucible product and simplifying the preparation process of the preform.

[0006] The objectives of the present invention are achieved through the following technical solutions.

[0007] An integrated crucible preform based on a single-layer structure is prepared by the following method:

[0008] (1) A carbon fiber web is needle-punched and laid on a core mold to form a web layer;

[0009] (2) spraying a layer of resin on the surface of the web layer to form a resin layer;

[0010] (3) Repeating steps (1) to (2) for multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0011] (4) curing the preform precursor obtained in step (3) to obtain an integrated crucible preform based on a single-layer structure.

[0012] Furthermore, the carbon fiber mat is a thin felt made of chopped carbon fiber with a surface density of 50 to 500 g / m 2 .

[0013] Furthermore, the needle punching density of the web layer is 10 to 50 needles / cm 2 The acupuncture depth is 5 to 10 mm.

[0014] Furthermore, the resin used for spraying the resin layer is furfural resin or phenolic resin.

[0015] Furthermore, the resin spraying amount of the resin layer is 0.5 to 1.5 L / cm 2 .

[0016] Furthermore, step (1) uses a soft core mold, which is convenient for needle punching, such as a wooden core mold or a rubber core mold; and before the curing treatment in step (4), the soft core mold is preferably replaced with a hard core mold, such as a metal core mold or a graphite core mold, to avoid deformation of the core mold during the curing treatment.

[0017] Furthermore, the curing conditions are as follows: curing pressure is 1.0-3.0 MPa, curing temperature is 100-250° C., and curing time is 3-5 h.

[0018] Furthermore, according to the structure of the integrated crucible, from the upper part to the lower part of the crucible along its depth direction, it is divided into a crucible straight section, a crucible R-angle transition section, and a crucible bottom surface. The thickness of the crucible straight section in the preform is less than the thickness of the crucible R-angle transition section, and the thickness of the crucible R-angle transition section is less than or equal to the thickness of the crucible bottom surface.

[0019] Furthermore, the thicknesses of the straight section of the crucible, the R-angle transition section of the crucible, and the bottom surface of the crucible in the preform are 200-500 mm, 300-600 mm, and 400-800 mm, respectively.

[0020] Furthermore, a layer of web layer and a layer of resin layer form a ply unit, and the thickness of a ply unit is 5 to 10 mm. The different thicknesses of different regions in the preform are achieved by different numbers of ply units.

[0021] Furthermore, the density of the preform is 0.30-0.50 g / cm 3 .

[0022] Beneficial effects:

[0023] (1) The present invention adopts a carbon fiber mesh with sprayed resin to prepare an integrated crucible preform. On the one hand, the sprayed resin can play a mechanical supporting role between the mesh layers after curing treatment, which not only improves the mechanical properties of the integrated crucible preform prepared based on the pure mesh single-layer structure, but also makes the preform structure hardened and not easy to deform, which is more conducive to transportation and storage; on the other hand, the uniform isotropic pure mesh layer serves as the inner surface of the integrated crucible preform, has a certain roughness and uniform surface quality, which is not only conducive to the preparation of the subsequent functional coating, but also improves the bonding performance between the functional coating and the crucible substrate, thereby solving the problem of affecting the service life of the crucible product due to the easy shedding of the functional coating.

[0024] (2) Compared with the preforms made of carbon fiber woven cloth, carbon fiber mesh and carbon fiber filaments, the process operation of the preform made of pure mesh in the present invention is simpler and the preparation cycle is short.

[0025] (3) The thickness of the ply unit of the present invention is large, the number of repetitions is small, and the preparation efficiency is high, but the uniformity of the pure web layer is difficult to ensure, which easily leads to reduced mechanical properties of the preform; on the contrary, if the thickness is small, the pure web layer is more uniform, but the number of repetitions is large, and the preparation efficiency is low. Therefore, the appropriate ply unit thickness can ensure the uniformity of the pure web layer in the preform and the overall preparation efficiency.

[0026] (4) Based on the structural characteristics of the crucible itself, it can be seen that the stress concentration is the greatest at the R corner, which is prone to fatigue cracks. Increasing the thickness here can effectively make the straight tube section transition smoothly to the bottom surface, reducing the stress concentration problem at the R corner; in addition, affected by the actual working conditions, the R corner and the bottom surface are most affected by the gravity of the silicon melt. Increasing the thickness of these two places can effectively prevent the occurrence of "silicon leakage"; and setting different thicknesses for different areas can effectively reduce the overall weight of the preform and reduce the manufacturing cost of the preform while ensuring the mechanical properties of the preform. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the structure of the integrated crucible preform based on the single-layer structure prepared in Example 1. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified. In addition, in the description of the present invention, it should be understood that the orientations or positional relationships indicated by the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc. are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation to the present invention.

[0029] Example 1

[0030] An integrated crucible preform based on a single-layer structure is prepared by the following method:

[0031] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0032] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 50g / m 2 The felt has a needle density of 10 needles / cm 2 , the needling depth is 5 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0033] (2) Spray a layer of furfural resin on the surface of the web layer at a spray volume of 0.5L / cm 2 , forming a resin layer; at this time, the web layer after spraying the furfural resin is a ply unit (comprising the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 5 mm;

[0034] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer units formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0035] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible from the upper part to the lower part along its depth direction. Different numbers of layer units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 200 mm, 300 mm, and 400 mm, respectively. It should be noted that the middle area of ​​the bottom surface of the crucible is usually provided with a supporting boss protruding to the outside of the crucible, such as Figure 1As shown, the support boss is formed by adding an additional number of layers to the support boss area during the layer laying process of the bottom surface of the crucible. The protruding thickness of the support boss can be in the range of 15 to 30 mm. Since the support boss does not affect the overall mechanical properties of the crucible, the present invention does not limit the support boss and can be set according to needs in practical applications.

[0036] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 1.0 MPa and a temperature of 250° C. for curing for 3 h to obtain a density of 0.30 g / cm 3 An integrated crucible preform based on a single-layer structure.

[0037] Example 2

[0038] An integrated crucible preform based on a single-layer structure is prepared by the following method:

[0039] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0040] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 300g / m 2 The felt has a needle density of 30 needles / cm 2 , the needling depth is 8 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0041] (2) Spray a layer of furfural resin on the surface of the web layer at a spray volume of 1.0 L / cm 2 , forming a resin layer; at this time, the web layer after spraying the furfural resin is a ply unit (comprising the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 8 mm;

[0042] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer unit formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0043] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 350 mm, 500 mm, and 600 mm, respectively.

[0044] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 2.0 MPa and a temperature of 180° C. for curing for 4 h to obtain a density of 0.40 g / cm 3 An integrated crucible preform based on a single-layer structure.

[0045] Example 3

[0046] An integrated crucible preform based on a single-layer structure is prepared by the following method:

[0047] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0048] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 500g / m 2 The felt has a needle density of 50 needles / cm 2 , the needling depth is 10 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0049] (2) Spray a layer of phenolic resin on the surface of the mesh layer at a spray volume of 1.5L / cm 2 , forming a resin layer; at this time, the web layer after spraying the phenolic resin is a ply unit (including the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 10 mm;

[0050] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer unit formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0051] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 500 mm, 600 mm, and 800 mm, respectively.

[0052] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 3.0 MPa and a temperature of 100° C. for curing for 5 h to obtain a density of 0.50 g / cm 3 An integrated crucible preform based on a single-layer structure.

[0053] The specific steps of performing subsequent densification treatment and coating a functional coating on the preform prepared in Example 3 to obtain a crucible product are as follows:

[0054] The preform obtained in step (4) of Example 3 was densified by chemical vapor infiltration combined with resin impregnation carbonization to obtain a density of 1.50 g / cm 3 A carbon / carbon composite crucible body is prepared; a glassy carbon coating with a thickness of 50 μm is prepared on the surface of the carbon / carbon composite crucible body by an impregnation curing-carbonization process, namely: first, furfural resin is impregnated at an impregnation pressure of 1 MPa for 0.5 h, then heated to 100°C at a heating rate of 1°C / h and cured at 100°C for 3 h, then heated to 900°C at a heating rate of 1°C / h and carbonized at 900°C for 5 h; yttrium oxide with a particle size of 100 μm is used as a raw material, and a plasma spraying process is used to prepare an yttrium oxide coating with a thickness of 500 μm on the surface of the glassy carbon coating, that is, the preparation of the crucible product is completed, wherein, in the spraying process, nitrogen is used as a protective gas, hydrogen is used as an anti-oxidation gas, and the nitrogen pressure is 3.0 MPa, the hydrogen pressure is 2.0 MPa, the voltage of the plasma arc used for spraying is 120 V, the current is 900 A, and the spraying distance is 30 mm.

[0055] The prepared crucible product was subjected to a thermal shock treatment from 1500°C to room temperature, and after 6 cycles, the coating on the carbon / carbon composite crucible body was still intact.

[0056] Comparative Example 1

[0057] An integrated crucible preform based on a single-layer structure is prepared by the following method:

[0058] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0059] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 50g / m 2 The felt has a needle density of 10 needles / cm 2 , the needle puncture depth is 5 mm, and the thickness of the ply unit is 5 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0060] (2) repeating the operation of step (1) multiple times, that is, continuing to use a carbon fiber web to perform needle punching and plying on the web layer obtained in step (1) to form a stacked structure of multiple web layers until the desired thickness of the preform is reached, thereby obtaining a preform precursor;

[0061] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of mesh layers are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 200 mm, 300 mm, and 400 mm respectively.

[0062] (3) The wooden core mold in the preform precursor obtained in step (2) was replaced with a graphite core mold, and then placed under a pressure of 1.0 MPa and a temperature of 250° C. for curing for 3 h to obtain a density of 0.25 g / cm 3 An integrated crucible preform based on a single-layer structure.

[0063] Comparative Example 1 is compared with Example 1, except that furfural resin is not sprayed on the web layer. The crucible preforms obtained in Example 1 and Comparative Example 1 were respectively subjected to mechanical property tests, that is, 5 test samples were taken from different areas of the crucible preform to be tested, each sample having a size of 40 mm×40 mm×50 mm, and then interlayer tensile strength tests were performed on different samples, and the average test results of the 5 samples were as follows:

[0064] Prefab Type Tensile strength(MPa) Crucible preform of Example 1 0.4 Crucible preform of Comparative Example 1 0.04

[0065] Comparative Example 2

[0066] An integrated crucible preform based on a single-layer structure is prepared by the following method:

[0067] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0068] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 300g / m 2 The felt has a needle density of 30 needles / cm 2 , the needling depth is 8 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0069] (2) Spray a layer of furfural resin on the surface of the web layer at a spray volume of 0.1L / cm 2 , forming a resin layer; at this time, the web layer after spraying the furfural resin is a ply unit (comprising the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 8 mm;

[0070] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer unit formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0071] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 350 mm, 500 mm, and 600 mm, respectively.

[0072] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 2.0 MPa and a temperature of 180° C. for curing for 4 h to obtain a density of 0.30 g / cm 3 An integrated crucible preform based on a single-layer structure.

[0073] Comparative Example 2 is compared with Example 2, only the spraying amount of furfural resin is reduced. The mechanical properties of the crucible preforms obtained in Example 2 and Comparative Example 2 were tested respectively, that is, 5 test samples were taken from different areas of the crucible preform to be tested, each sample had a size of 40 mm×40 mm×50 mm, and then the interlayer tensile strength test was performed on different samples, and the average test results of the 5 samples were as follows:

[0074] Prefab Type Tensile strength(MPa) Crucible preform of Example 2 0.5 Crucible preform of comparative example 2 0.05

[0075] Comparative Example 3

[0076] An integrated crucible preform based on a single-layer structure is prepared by the following method:

[0077] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0078] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 500g / m 2 The felt has a needle density of 50 needles / cm 2 , the needling depth is 20 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0079] (2) Spray a layer of phenolic resin on the surface of the mesh layer at a spray volume of 1.5L / cm 2 , forming a resin layer; at this time, the web layer after spraying the phenolic resin is a ply unit (including the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 20 mm;

[0080] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer unit formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0081] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 500 mm, 600 mm, and 800 mm, respectively.

[0082] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 3.0 MPa and a temperature of 100° C. for curing for 5 h to obtain a density of 0.45 g / cm 3 An integrated crucible preform based on a single-layer structure.

[0083] Compared with Example 3, Comparative Example 3 is only thicker in thickness of the layer unit and less in number of repetitions. The crucible preforms obtained in Example 3 and Comparative Example 3 were respectively subjected to mechanical property tests, that is, 5 test samples were taken from different areas of the crucible preform to be tested, each sample having a size of 40 mm×40 mm×50 mm, and then interlayer tensile strength tests were performed on different samples. The average test results of the 5 samples are as follows:

[0084] Prefab Type Tensile strength(MPa) Crucible preform of Example 3 0.8 Crucible preform of comparative example 3 0.6

[0085] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An integrated crucible preform based on a single-layer structure, characterized in that: The preform is prepared by the following method: (1) A carbon fiber web is needle-punched and laid on a core mold to form a web layer; (2) spraying a layer of resin on the surface of the web layer to form a resin layer; (3) Repeating steps (1) to (2) for multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor; (4) curing the preform precursor obtained in step (3) to obtain an integrated crucible preform based on a single-layer structure.

2. The integrated crucible preform based on the single-layer structure according to claim 1, characterized in that: The carbon fiber mat is a thin felt made of chopped carbon fiber with a surface density of 50 to 500 g / m 2 ; Or / and, the needle punching density of the web layer is 10 to 50 needles / cm 2 The acupuncture depth is 5 to 10 mm.

3. The integrated crucible preform based on a single-layer structure according to claim 1, characterized in that: The resin used for spraying the resin layer is furfural resin or phenolic resin; Or / and, the resin spraying amount of the resin layer is 0.5-1.5L / cm 2 .

4. The integrated crucible preform based on a single-layer structure according to claim 1, characterized in that: The soft core mold is used in step (1), and the soft core mold needs to be replaced with a hard core mold before the curing treatment in step (4).

5. The integrated crucible preform based on the single-layer structure according to claim 4, characterized in that: The soft core mold is a wooden core mold or a rubber core mold; The hard core mold is a metal core mold or a graphite core mold.

6. The integrated crucible preform based on a single-layer structure according to any one of claims 1 to 5, characterized in that: The curing conditions are as follows: curing pressure is 1.0-3.0 MPa, curing temperature is 100-250° C., and curing time is 3-5 h.

7. The integrated crucible preform based on a single-layer structure according to claim 1, characterized in that: According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible from the upper part to the lower part along its depth direction. The thickness of the straight section of the crucible in the preform is less than the thickness of the R-angle transition section of the crucible, and the thickness of the R-angle transition section of the crucible is less than or equal to the thickness of the bottom surface of the crucible.

8. The integrated crucible preform based on a single-layer structure according to claim 7, characterized in that: The thickness of the straight tube section of the crucible, the R-angle transition section of the crucible and the bottom surface of the crucible in the preform are 200-500 mm, 300-600 mm and 400-800 mm respectively.

9. The integrated crucible preform based on a single-layer structure according to any one of claims 1-3, 7-8, characterized in that: A layer of web layer and a layer of resin layer constitute a ply unit, and the thickness of a ply unit is 5 to 10 mm.

10. The integrated crucible preform based on a single-layer structure according to claim 9, characterized in that: The density of the preform is 0.30-0.50 g / cm 3 .